Гидратированные оксиды элементов IV и V групп - Плетнев Р. Н. Рафаэль Николаевич; Ивакин А. А. Анатолий Александрович; Бурмистров В. А. Владимир Александрович; Денисова Т. А. Татьяна Александровна; Клещев Д. Г. Дмитрий Георгиевич; Егоров Ю. В. Юрий Вячеславович (Москва, Наука, 1986)
Авт. указаны на обороте тит. л.